Analisis Kandungan Hara N, P, dan K pada Perbedaan Lahan yang Ditanami Karet dan Kelapa Sawit - Nur Hidayanti; Muhammad Mahbub; Abdul Haris (Acta Solum, 2024)
The general obstacles in cultivating rubber and oil palm are soil acidity and limited availability of nutrients, especially N, P, and K. These nutrients play an important role in the growth of rubber and oil palm plants. Knowing the nutrient content is necessary to be able to determine the management that needs to be carried out. The objective of this study is to determine differences in the nutrient content of N, P, and K on various lands planted with rubber and oil palm plants. Soil sample analysis was conducted in the laboratory for available N, available P, and available K. To determine differences in land use for the elements N, P and K, data were analyzed using an unpaired two sample t test. The results showed differences in available K and available P levels between the two land types, while no differences were observed in N availability between the two land types. This variation may be caused by differences in land management practices.